Tobacco related cancers at a tertiary care hospital in Western India - Agrawal, K; Rajderkar, SS; Tuljapurkar, V (Health Renaissance, 2013)
Background: Tobacco related cancers represent the most preventable form of cancer in our society. Objective: To determine the proportion of tobacco related cancers among male and female cancer patients at a tertiary cancer care hospital in Western India. Methods: This is a retrospective patient record based retrieval type of study which was conducted at a leading tertiary cancer care hospital of Western India. Analysis of case records of all cancer patients admitted at the Shri Siddhivinayak Ganapati Cancer Hospital, Miraj, Maharashtra, (India) over a 24-month period was done. The case records of total three thousand five hundred and two (3502) cancer patients were retreived and analysed to know the proportion of tobacco related cancers. Data obtained ware analysed using SPSS version 16.0 and presented in the form of percentages and proportions. Chi square test of significance was used. Results: The total proportions of tobacco related cancers (TRCs) among male and female subjects combined togethe was 22.8%. The proportion of TRCs in male was 33.1%, while in female it was 12.5%. Oral cancers and oesophageal cancers were the leading sites among the TRCs in male and female respectively. Conclusion: One third of all cancers in men occurred in the sites associated with tobacco use (TRCs). In women, one eighth of cancers occurred at these sites. Health Renaissance, January-April 2013; Vol. 11 No.1; 43-46 DOI: http://dx.doi.org/10.3126/hren.v11i1.7601